2018
DOI: 10.1111/acer.13610
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Temporal Typology of Alcohol Hangover

Abstract: BackgroundAt a group level, hangover severity during the day has been described to follow an inverted U‐shaped curve, with gradually increasing severity scores that, after reaching a peak, gradually decrease toward zero. The aim of this study was to examine if and how individual drinkers' hangover severity scores vary during the day.MethodsData from a survey (Penning et al., 2012) in which 727 drinkers reported on their latest alcohol hangover were reanalyzed. The temporal pattern of each individual's hangover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…For example, research showed that short term memory is superior early in the morning and deteriorates over the day (Baddeley, Hatter, Scott, & Snashall, 1970). Also, hangover severity varies during the day, and different severity patterns have been identified to characterize drinkers (Verster et al, 2018). Although we aimed to test a participant at approximately the same time of day on the hangover and control day, given the naturalistic design this was not always achieved.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research showed that short term memory is superior early in the morning and deteriorates over the day (Baddeley, Hatter, Scott, & Snashall, 1970). Also, hangover severity varies during the day, and different severity patterns have been identified to characterize drinkers (Verster et al, 2018). Although we aimed to test a participant at approximately the same time of day on the hangover and control day, given the naturalistic design this was not always achieved.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of AH is further complicated by individual variation in hangover symptom frequency and severity [ 43 , 44 ], of which, genetic variations contribute about 40%–45% [ 45 ]. The influence of genetic variations on AH is evident when considering the efficacy of Korean pear juice, which has been shown to effectively reduce certain AH symptoms according to aldehyde dehydrogenase (ALDH) genotype.…”
Section: Introductionmentioning
confidence: 99%
“…There can be considerable inter-individual variability in the pattern, severity, and temporal characteristics of hangover symptoms [8], with no clear relationship between AH severity and any single physiological process (although cytokine response to alcohol is emerging as a possible key factor [9,10]). Other mechanisms that may contribute to AH include, but are not limited to, gut dysbiosis (including ghrelin-mediated), decreased blood glucose concentrations, poor sleep architecture, dehydration (and concomitant electrolyte imbalances), oxidative stress, and inflammatory responses [2,11,12].…”
Section: Introductionmentioning
confidence: 99%